Jordan - Resolving Jordan's Labor Market Paradox of Concurrent Economic Growth and High Unemployment - World Bank (Washington, DC, 2014)
Reducing unemployment is a top priority of the Government of Jordan, as expressed in its principal strategies, "we are all Jordan" and the national agenda. Consistent with those strategies and with the recommendations of donors, the Government's approach to reducing unemployment has been to create jobs by attracting investments that promote gross domestic product (GDP) growth. In recent years, Jordan has successfully attracted investment, achieved strong GDP growth, and created many new jobs. This report also recommends actions to further the Government's goal of reducing employment. To accomplish this we cover industrial policy, fiscal policy, regional development, education, and social protection programs. Although this report comments on employment aspects of several policies and programs, truly comprehensive analysis of these policies and programs is beyond its scope. Rather, these findings and recommendations should be considered in the context of ongoing work by the Government, the World Bank, and other donors the various policy and program areas. That work includes analytical work and investments in the areas of: (a) public expenditure, (b) financial sector functioning, (c) investment climate, (d) poverty mapping, and (e) pension reform. It also includes projects in: (a) higher education development, (b) education reform for the knowledge economy, (c) social protection, (d) employer-driven skills development, and (e) regional and local development.